Comparison of Visual and Digital Color Measurement Methods on Anterior Natural Teeth - Eryürük Sait Ege; Hekimoğlu Canan; Akçin Elif Tuba; Çavuşoğlu Yeliz (Balkan Stomatological Society, 2018)
Background/Aim: The purpose of this study was to evaluate compatibility between visual and digital color measurement methods.